2002
DOI: 10.1021/es025884w
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Atmospheric Mercury Species at a Coastal Site in the Antarctic and over the South Atlantic Ocean during Polar Summer

Abstract: Mercury and many of its compounds behave exceptionally in the environment because of their volatility, capability for methylation, and subsequent biomagnification in contrast with most of the other heavy metals. Long-range atmospheric transport of elemental mercury, its transformation to more toxic methylmercury compounds, the ability of some to undergo photochemical reactions, and their bioaccumulation in the aquatic food chain have made it a subject of global research activities, even in polar regions. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
180
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(205 citation statements)
references
References 40 publications
23
180
2
Order By: Relevance
“…Alternatively, tests on ground are not representative for the conditions at flight altitudes. But the RGM transmission is consistent with findings of Temme et al (2003) who reported quantitative RGM transmission of PFA tubing at low temperature and dry air conditions encountered in Antarctica. These conditions are similar to conditions in UT/LS.…”
Section: Resultssupporting
confidence: 90%
“…Alternatively, tests on ground are not representative for the conditions at flight altitudes. But the RGM transmission is consistent with findings of Temme et al (2003) who reported quantitative RGM transmission of PFA tubing at low temperature and dry air conditions encountered in Antarctica. These conditions are similar to conditions in UT/LS.…”
Section: Resultssupporting
confidence: 90%
“…The range of data is coherent with previous data measured in January 2009 at DC (Dommergue et al, 2012). The median concentration is significantly lower than measurements made on the Greenland ice cap (Faïn et al, 2008) but comparable to values retrieved both at coastal sites of Antarctica such as Neumayer Station (0.99±0.27 ng.m -3 (Ebinghaus et al, 2002, Temme et al, 2003, Terra Nova Bay (0.9±0.3 ng.m -3 (Sprovieri et al, 2002)), McMurdo (1.20±1.08 ng.m -3 (Brooks et al, 2008b) and the continental South Pole station 0.54 ± 0.19 ng.m -3 (Brooks et al, 2008a).…”
Section: Resultssupporting
confidence: 75%
“…The Nieuw Nickerie means are the same as in Table 1. On the one hand, the decrease of mercury concentrations from North to South seems to be rather continuous, as formerly indicated by data obtained during ship cruises (Temme et al, 2003). On the other hand, Slemr et al (1985) hypothesized that TGM is rather uniformly distributed over the SH.…”
Section: Continental Mercury Sourcesmentioning
confidence: 64%